The effects of hydrometeorological disaster and potential conflicts on the human development index using linear mixed multilevel models - Zevic, Farell Fillyanno; Rachmawati, Ro'fah Nur; Djunet, Ghina Nisrina; Almutawakkil, Fauzan Naufal (Universitas Islam Negeri Raden Intan Lampung, 2023)
As is generally known, the human development index (HDI) is formed from three main factors, namely education, health, and income, which measure the population's access to a decent standard of living. Using the linear mixed multilevel models, this study indicates that other factors beyond these three basic dimensions of HDI, namely hydrometeorological disasters and potential conflicts, significantly affect the HDI value. This research focuses on longitudinal data analysis from 27 regencies and cities in West Java, Indonesia, in the last four years until 2022, with the level of hydrometeorological disasters consistently increasing every year and an increasing trend in the number of potential conflicts. The dimensions of human life and other factors can affect the human development index, namely the number of hydrometeorological disasters and potential conflicts, which have a negative correlation so that the value of the HDI can be reduced if the intensity of hydrometeorological disasters increases and possible conflicts can be controlled. Moreover, this study shows that uncontrolled potential conflicts in each regency or city from time to time can reduce HDI values. Therefore, this research can be a reference for the government, stakeholders, and the community in carrying out work programs that are right on target to increase HDI consistently every year.